Linking Company’s Activity and Human Well-Being from the Perspective of Corporate Social Responsibility - Skruibytė, Izolda (Social Welfare: Interdisciplinary Approach, 2023)
There is growing interest from academic scholars and international institutions in assessing the impact of business activity on human well-being. Business is essential for our lives but it is still unclear what companies’ activities should be to increase standards of living and to contribute better to higher human well-being. What is the role of corporate social responsibility (CSR) on human well-being, and how can companies be motivated towards more responsible activities? Partly, it is a matter of subjective understanding and, partly, a matter of assessing the phenomena of human well-being and CSR tends to make these relations more complicated and more scientific discussions are needed, therefore, to address these issues. The present study represents a comprehensive analysis of the concept of human well-being from the perspectives of both hedonic and eudaimonic approaches and it also investigates the role of CSR in companies’ economic activities, as well as outlines the theoretical links between CSR and human well-being. A conceptual model of the links between company’s economic activity and human well-being, according to CSR, is provided. The model states that the contribution of a business to human well-being differs depending on whether company’s activity is concentrated on economic results, or rather on sustainable development. The responsible activity of a company that meets the environmental, social, and economic challenges when producing goods and providing services contributes positively to human well-being in the long term. CSR contributes to society by enabling companies to satisfy the expectations of society and it also strengthens the likelihood that a society can achieve higher living standards and sustainable development as well.
Keywords: corporate social responsibility; human well-being; life satisfaction; economic welfare